Associations between particulate matter composition and childhood blood pressure — The PIAMA study. (November 2015) - Bilenko, Natalya; Brunekreef, Bert; Beelen, Rob; Eeftens, Marloes; de Hoogh, Kees; Hoek, Gerard; Koppelman, Gerard H.; Wang, Meng; van Rossem, Lenie; Gehring, Ulrike
Abstract: Background: Childhood blood pressure is an important predictor of hypertension and cardiovascular disease in adulthood. Evidence for an association between ambient particulate matter (PM) exposure and blood pressure is increasing, but little is known about the relevance of different PM constituents. Objectives: We investigated the association between particulate matter composition and blood pressure at age 12 years. Methods: Annual average concentrations of copper, iron, potassium, nickel, sulfur, silicon, vanadium, and zinc in particles with diameters of less than 2.5 μm (PM2.5 ) and 10 μm (PM10 ) were estimated by land-use regression modeling for the home addresses of the participants of the prospective PIAMA birth cohort study. Associations between element concentrations and blood pressure measurements performed at age 12 years were investigated by linear regression with and without adjustment for confounders. Results: After adjustment for potential confounders we found statistically significant positive associations of diastolic blood pressure with iron, silicon, and potassium in PM10 in children who lived at the same address since birth [mean difference (95% confidence interval) 0.67 (0.02;1.31) mm Hg, 0.85 (0.18;1.52) mm Hg, and 0.75 (0.09;1.41) mm Hg, respectively, per interquartile range increase in exposure]. Also, we found marginally significant (p < 0.1) positive associations between iron and silicon in PM2.5 and diastolic blood pressure. Part of the observed effects was found to be attributable to NO2, a marker of exhaust traffic emissions. Conclusions: Exposure to particulate matter constituents, in particular iron may increase blood pressure in children. The possible association with iron may indicate the health relevance of non-exhaust emissions of traffic. Highlights: Childhood blood pressure is a predictor of adulthood cardiovascular disease The role of ambient particulate matter constituents for blood pressure is unknown. In particular iron and silicon in PM was associated with diastolic blood pressure. The association with iron indicates the relevance of non-exhaust traffic emissions.